Sustainable fiber reinforced cementitious panels containing PCM: Mechanical and thermal performance - Tuncel, Yigit; Pekmezci, Bekir (Revista ALCONPAT, 2020)
An experimental study was planned and executed for the application of Phase Change Materials (PCM) containing fiber-reinforced cementitious panels on buildings. The objective of the research was to enhance the thermal performance of the panels. Panels with the dimensions of 60x120x2.5 cm were produced and experimental investigations about the thermal and the mechanical performance of the composites were carried out. PCM containing composites showed higher latent heat capacity and lower thermal conductivity. Reinforcement with chopped fibers compensated the strength loss due to PCM in cementitious panels. Specific fracture energy of the panels increased with increase of PCM ratio. PCM containing fiber reinforced cementitious panels showed great potential for energy efficient buildings with enhanced thermal and mechanical properties.